Trophic Relationships and Structure of Brackish Water and Coastal Ecosystems: Possible Common Trends between African and Asian Waterbodies - LALEYE, PHILIPPE A. (My University, 2021)
In the present synthesis, trophic relationships of eight coastal and brackish ecosystems in some countries of Africa and Asia were reviewed (Ivory Coast, Benin, Senegal, in Africa, Sri Lanka, Vietnam, Thailand and China in Asia). For these highly productive and complex ecosystems, knowledge on the biological and ecological functioning of fish faunas utilizing, as well as, the environmental forces contributing to geographic specificities of these environments is vital for their sustainable management and conservation. Recognizing that anthropogenic activities impact not only the environment but the dynamics and functioning of its living resources, untangling ecosystem processes can increase understanding of its current health and resilience to change. Effective management of these ecosystems should focus on a framework based on a sound understanding of ecosystem
Keywords: Ecopath with Ecosim; Mass balance models; Small-scale fisheries; Tropical fisheries